White House secrets : medical lies and cover-ups - Jarrow, Gail (Jarrow, Gail. Medical fiascoes series., 2025)
"Too often when a president is sick or dying, he and the people around him have hidden his condition from the public, wanting to project an image of strength and power. Gail Jarrow explores the shocking, yet true, stories of presidential medical cover-ups from the 19th through the 21st centuries"-- Provided by publisher.